FRAGMENTATION OF AUTHORITY TOWARDS NETWORKED LEADERSHIP: Reconstructing the Role of Pre-Adaptive Educational Leaders at the Beginning of Digital Disruption - Siswadi; MR Supean Chemo (TSURAYYA: Journal Education, Economy and Religia, 2026)
This article aims to analyze the phenomenon of authority fragmentation in educational leadership and reconstruct the role of educational leaders toward a network-based and pre-adaptive leadership model in the early phase of digital disruption. The transformation occurring around 2016–2019 indicates a significant shift from hierarchical leadership structures to more open, collaborative, and network-oriented systems. This study employs a qualitative approach using library research by analyzing relevant academic literature. The findings reveal that digitalization has accelerated the fragmentation of authority, where influence and decision-making are no longer centralized but distributed across multiple network nodes. This condition requires a transformation from authority-based leadership to influence-based, collaborative, and connective leadership. Furthermore, this study emphasizes the importance of pre-adaptive leadership, which not only responds to change but also anticipates and prepares organizations for future uncertainties. The reconstruction of educational leadership roles includes functioning as network connectors, innovation facilitators, sense-makers, and change navigators. Therefore, leadership in the early digital disruption era is no longer defined by formal power but by the ability to build relationships, manage complexity, and drive collective change.